2000
DOI: 10.1046/j.1525-1497.2000.03359.x
|View full text |Cite
|
Sign up to set email alerts
|

The doctor-patient relationship and HIV-infected patients’ satisfaction with primary care physicians

Abstract: OBJECTIVE:To assess the extent to which perceptions of specific aspects of the doctor-patient relationship are related to overall satisfaction with primary care physicians among HIV-infected patients. DESIGN: MEASUREMENTS AND MAIN RESULTS:The primary outcome measure was patient-reported satisfaction with a primary care physician measured 6 months after initiating primary HIV care. Patients who were more comfortable discussing personal issues with their physicians ( P ‫؍‬ .021), who perceived their primary car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 29 publications
2
51
1
4
Order By: Relevance
“…Sood et al, Beach et al, Sullivan et al 5,15,20 These similarities in mean age seen at the ART clinics may reflect the fact that most people present to the clinic within the age range of 31 to 40 years & most of the participants belonged to the same age group in this study (42.5%). Patients who reported their provider knows them ""as a person"" were older.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Sood et al, Beach et al, Sullivan et al 5,15,20 These similarities in mean age seen at the ART clinics may reflect the fact that most people present to the clinic within the age range of 31 to 40 years & most of the participants belonged to the same age group in this study (42.5%). Patients who reported their provider knows them ""as a person"" were older.…”
Section: Discussionmentioning
confidence: 50%
“…The strong predictors of satisfaction with the ART services were education attainment and age in study done in Nigeria similar to this study. 23 While higher satisfaction with the primary care physician was found among women, patients with lower income and those reporting better health status in study done by Sullivan et al 5 Lower satisfaction with ""quality and convenience"" was found in men, the richest group, and in patients who had higher CD4 cell counts in study done in Vietnam. 22 The chronicity of the disease requires constant care and treatment facilities puts a lot of financial burden on the patient.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…It is therefore possible that patients in better health perceived their communication with doctors as more concordant. One study found that patients with less intense symptoms were more satisfied with their care [36], although this finding was not replicated in a later study [37]. However, research has shown that patients with better self-rated health were more likely to be consumerist [38] and thus likely to have higher expectations of medical care, which should lead to perceiving doctors as less concordant.…”
Section: Discussionmentioning
confidence: 95%